Chronic tedium in the contemporary subject. Study of ’ennui’ in ’La grande bellezza’ (Paolo Sorrentino, 2013) - Mendieta Rodríguez, Elios (Escritura e Imagen, 2019)
This article looks for an approach to ennui or chronic tedium in the present, using Jep Gambardella as a model, the main character of the film La grande bellezza (The Great Beauty, 2013), directed by Paolo Sorrentino. In a beginning, a theoretical and historical approach of the ennui will be made. Then, and before entering into the analysis of the character of the film, I study the work of creators such as Ennio Flaiano, Michelangelo Antonioni or Jean Luc Godard, whose characters –constantly boring, apathetic and jaded– have served as an essential reference point in Sorrentino’s work. Finally, I update the taedium vitae in the present.